Human papillomavirus vaccination at age 9 or 10 years to increase coverage – a narrative review of the literature, United States 2014–2024 - Sarah K. Brewer; Ruth Stefanos; Neil C. Murthy; Amimah F. Asif; Shannon Stokley; Lauri E. Markowitz (Human Vaccines & Immunotherapeutics)
The Advisory Committee on Immunization Practices recommends routine human papillomavirus (HPV) vaccination at 11–12 years; the series can begin at age 9. U.S. HPV vaccination coverage is lower than other adolescent vaccinations. One proposed strategy to increase coverage is initiation at 9–10 years. We systematically reviewed studies addressing vaccination at age 9 to identify and evaluate evidence regarding potential programmatic advantages. Among 30 publications from 2014 to 2024 there were retrospective cohort studies (N = 11), intervention studies with a component focused on vaccination at 9–10 (N = 12), and studies of feasibility or acceptability by providers or caregivers (N = 7). While retrospective analyses found earlier initiation associated with completion, limitations in methodology preclude a cause-and-effect interpretation. Impact of age 9 vaccination is difficult to isolate in intervention studies that had multiple components. While initiating vaccination at age 9 is feasible, questions remain regarding the benefit of this approach to increase coverage.